Introduction to radio frequency design. - Hayward, Wes, ....- (Newington : American Radio Relay League, 2004)
A thorough treatment of the fundamental methods of radio frequency design using mathematics as needed to develop intuition for RF circuits and systems. You'll find emphasis on applications of simple circuit models whenever possible. Prepares readers to actually design HF, VHF and UHF equipment.
Keywords: Telecommunicatietechniek